Nitrogen-doped graphene as an efficient metal-free catalyst for ammonia and non-enzymatic glucose sensing - Raza, Waseem; Ahmad, Khursheed; Kim, Haekyoung (Journal of Physics and Chemistry of Solids, 2022)
Theoretical studies reveal that the electronic and chemical properties of graphene can be significantly altered by chemical doping with a nitrogen atom. In the present work, a unique strategy has been applied for the manu-facture of selective N-doped graphene (NG). A low cost, and facile one pot solvothermal approach has been adopted for the synthesis p-type nitrogen graphene. Moreover, the as-synthesized NG sheets exhibit a crossover from n-type to p-type behaviour. The presence of pyridinic-N in graphene planes is confirmed by high-resolution X-ray photoelectron spectroscopy. The as-synthesized NG presents excellent sensing properties towards ammonia, and fast electron transfer kinetics for glucose oxidase. The higher sensing activity is ascribed to synergistic effect of nitrogen, and oxygen-containing functional groups. The resultant NG is proven to act as a metal-free catalyst with much better performance for ammonia and glucose sensing at room temperature. This study will provide a promising potential for the development of NG type sensors in the real world and envi-ronmental applications.
CRIS-Team WoS Importer:2021-11-05